Hip Joint Kinematic Covariation During Gait Before and 1-Year After Hip Arthroscopic Surgery for Femoroacetabular Impingement Syndrome - Malloy, Philip; Dr. Neumann, Donald; Leung, Anne; Kipp, Kristof (Frontiers in Surgery, 2021)
The primary aim of this study was to determine if the three-dimensional (3D) hip joint motion coordination during gait changes after arthroscopic surgery for femoroacetabular impingement syndrome (FAIS). Three-dimensional hip joint kinematic data were collected with a 12-camera motion capture system. Five trials of level walking were collected preoperatively (PRE) and at 1-year postoperatively (POST) in 8 patients diagnosed with FAIS and at a single time point in 8 healthy controls. Planar covariation analysis was performed to quantify the 3D hip joint motion coordination strategy during gait. Independent sample's t-test were used to determine differences between the FAIS group at the preoperative time point (PRE) and healthy controls. Paired samples t-tests were used to determine differences between the PRE and POST time points within the FAIS group. The %VAF by PC 1 for the FAIS group at the PRE time point was significantly less than that of healthy controls (PRE: 77.2 ± 8.7% vs. Control: 96.1 ± 2.8%; p = 0.0001), and the % VAF of the second PC (PC2) was significantly greater [PRE: 22.8 (8.7)%; Control: 3.9 (2.8)%; p = 0.0001]. No differences in %VAF were found between the PRE and POST time points within the FAIS group for PC1 [PRE: 77.2 (8.7)% vs. POST: 79.3 (11.1)%; p = 0.472] or PC2 [PRE: 22.7 (8.7)%; POST: 20.7 (11.1)%; p = 0.472]. Significant differences in the plane specific contribution to the 3D motion coordination strategy were found between the FAIS patients at the PRE and POST time points for the sagittal plane [PRE: 5.6 (2.7) vs. POST: 0.91 (6.1); p = 0.012] and frontal plane [PRE: −10.4 (2.2) and −1.5 (6.3); p = 0.005]. Patients with FAIS demonstrated a more complex coordination strategy of 3D hip joint motion than controls and this strategy remains unchanged after hip arthroscopic surgery despite changes in the plane specific contribution to this strategy. These findings indicate that motor control impairments in FAIS patients do exist and seem to persist for at least 1 year after hip arthroscopic surgery.